ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS V SD NEGERI 1 GUBUKUSUMA - Sarmin Muhtar; Samsu Somadayo; Selvi Wulandari (PEDAGOGIK, 2022)
The purpose of this study was to determine the reading comprehension ability of fifthgrade students of SD Negeri 1 Gubukusuma. This research is a qualitative descriptivestudy, which is a research technique that describes and interprets the data that has beencollected by paying attention to the aspects assessed by the data collection techniqueusing observation, test, and documentation techniques. Data analysis in this study usedquantitative qualitative techniques.The results of this study indicate the ability to read comprehension in fifth grade studentsof SD Negeri 1 Gubukusuma seen in the data on student ability test results, from 15students the maximum score obtained was 100% with very good qualifications, and aminimum score of 75% in the sufficient category, and the acquisition of grades theaverage score reached 87% with a good category and met the minimum completenesscriteria.